1996
DOI: 10.1097/00001648-199601000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Factors and Risk of Breast Cancer

Abstract: A high level of endogenous estrogen in utero has been hypothesized to be a possible risk factor for breast cancer. We used information from two population-based case-control studies to investigate the relation between perinatal factors and risk of invasive breast cancer among women age 21-45 years (746 cases, 960 controls) and women age 50-64 years (401 cases, 439 controls). Breast cancer cases were ascertained through a population-based cancer registry, and controls were selected by random digit dialing. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
165
4
2

Year Published

2000
2000
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(191 citation statements)
references
References 35 publications
20
165
4
2
Order By: Relevance
“…These studies show that women who were exposed to high foetal oestrogenic environment; that is, had a high birth weight or are twins, are at an increased risk of developing breast cancer (Braun et al, 1995;Michels et al, 1996;Sanderson et al, 1996;Weiss et al, 1997). At a particularly high risk are twins whose birth weight was high (Hubinette et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…These studies show that women who were exposed to high foetal oestrogenic environment; that is, had a high birth weight or are twins, are at an increased risk of developing breast cancer (Braun et al, 1995;Michels et al, 1996;Sanderson et al, 1996;Weiss et al, 1997). At a particularly high risk are twins whose birth weight was high (Hubinette et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that women who were born after preeclamptic pregnancies have a reduced risk of breast cancer in adult life (Ekbom et al, 1992(Ekbom et al, , 1997Sanderson et al, 1996). Several studies have also suggested that low birth weight may be associated with reduced breast cancer risk (Ekbom et al, 1992;Michels et al, 1996;Stavola et al, 2000).…”
Section: Epidemiologymentioning
confidence: 99%
“…Conversely, high adolescent (Coates et al, 1999;Hislop et al, 1986;Le Marchand et al, 1988a), early adult (Coates et al, 1999;Huang et al, 1997;Trentham-Dietz et al, 1997) and adult weight or body mass index (Brinton and Swanson, 1992;Huang et al, 1997;Swanson et al, 1996;Ursin et al, 1995;van den Brandt et al, 2000) appear to be protective against premenopausal breast cancer. Several studies have investigated the association between breast cancer and weight at birth (De Stavola et al, 2000;Ekbom et al, 1992Ekbom et al, , 1997Innes et al, 2000;Le Marchand et al, 1988b;Michels et al, 1996;Sanderson et al, 1996Sanderson et al, , 1998a or weight at adolescence (Brinton and Swanson, 1992;Choi et al, 1978;Coates et al, 1999;Franceschi et al, 1996;Hislop et al, 1986;Le Marchand et al, 1988a;Pryor et al, 1989) with inconsistent findings. Possible limitations of these studies related to exposure measurement and age at diagnosis of breast cancer.…”
mentioning
confidence: 99%